2022
DOI: 10.3390/life12081280
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacterial Communities from the Surface and Adjacent Bottom Layers of Water in the Billings Reservoir

Abstract: Here, we describe the bacterial diversity and physicochemical properties in freshwater samples from the surface and bottom layers of the Billings Reservoir, the largest open-air storage ecosystem in the São Paulo (Brazil) metropolitan area. Forty-four samples (22 from the surface and 22 from the bottom layers) were characterized based on 16S rRNA gene analysis using Illumina MiSeq. Taxonomical composition revealed an abundance of the Cyanobacteria phylum, followed by Proteobacteria, which were grouped into 190… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Previous studies primarily focused on physicochemical variables and the presence of bacterial strains using culture-dependent methods 22 , 26 29 . Recent culture-independent studies conducted by our group revealed a higher prokaryotic diversity in Billings Reservoir compared to similar water systems and also a high abundance of cyanobacteria 24 , 30 . These bacteria are considered the most widespread photosynthetic organisms due to their global distribution and their significant ecological presence in nutrient-rich habitats, which often lead to the formation of blooms 31 .…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Previous studies primarily focused on physicochemical variables and the presence of bacterial strains using culture-dependent methods 22 , 26 29 . Recent culture-independent studies conducted by our group revealed a higher prokaryotic diversity in Billings Reservoir compared to similar water systems and also a high abundance of cyanobacteria 24 , 30 . These bacteria are considered the most widespread photosynthetic organisms due to their global distribution and their significant ecological presence in nutrient-rich habitats, which often lead to the formation of blooms 31 .…”
Section: Introductionmentioning
confidence: 79%
“…At the beginning of the study, the geographic coordinates of the collection sites were recorded to ensure that subsequent water samples and measurements were taken on water from specific locations. Collected samples were stored in cool boxes at 4 °C in the dark and transported to the laboratory, where they were immediately processed as previously described 24 , 30 . The number of sites on the reservoir and their locations are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations